School of Neurology in the medicine of 1857-2003 - Dumitrașcu, Dumitru (Medicine and Pharmacy Reports, 2013)
Kory Ştefania Calomfirescu Risoprint Publishing, Cluj-Napoca, 2012 203 pages, ISBN 978-973-53-0843-8